Criteria for validating polaron pair dissociation in polymer-fullerene bulk heterojunction solar cells - Inche Ibrahim, Mohd Lukman (American Institute of Physics Inc., 2016)
The dissociation of polaron pairs into free charge carriers in organic bulk heterojunction solar cells is a fundamental step in generating photocurrent and is still in debate. In this study, we propose two simple criteria that can be used to test the validity of any polaron pair dissociation model for polymer-fullerene bulk heterojunction solar cells. The first criterion states that the ratio of the bimolecular recombination current density to the maximum photocurrent density should increase as a function of applied voltage. The second criterion states that the ratio of the bimolecular recombination current density to the maximum photocurrent density at short circuit should not be larger than 1. We apply these criteria to test the validity of the widely used Onsager-Braun model by using the experimental current-voltage data of poly[2-methoxy-5-(30-70-dimethyloctyloxy)-p-phenylene vinylene] (OC1C10-PPV) and [6,6]-phenyl C61-butyric acid methylester (PCBM) based solar cells. We find that our numerical analysis is not suitable to employ these criteria. Our analytical analysis, on the other hand, clearly demonstrates that the Onsager-Braun model simply cannot fulfill the first criteria. The reason is because the polaron pair dissociation given by the Onsager-Braun model is too strongly influenced by the electric field (i.e., decreases too rapidly as the electric field decreases). The analysis provides a further evidence against the widely used Onsager- Braun model. The proposed criteria can help us to determine the correct model for polaron pair dissociation by serving as a guideline on how strongly the electric field is allowed to influence the polaron pair dissociation.